Assistência pré-natal e fatores associados à peregrinação no anteparto e à preferência das mulheres pela cesariana em Sergipe, Brasil - Mendes, Rosemar Barbosa (2018)
The Ministry of Health through the Prenatal and Birth Humanization Program (PHPN) establishes the minimum procedures that should be offered to all pregnant women during prenatal care, as well as ensuring the right of these women to be linked to maternity care service to give birth for preventing the antenatal peregrination. In this perspective, the objective of this study was to evaluate the quality of prenatal care and the factors associated with antenatal peregrination and women's preference for cesarean section in Sergipe, Brazil. It was realized a cross-sectional and quantitative study, with descriptive and analytic approach, using survey data from the Birth in Sergipe, research conducted between June/2015 and April/2016. A total of 768 postpartum women were evaluated, proportionally distributed among all maternity hospitals in the state. For statistical analysis were used the Chi-square test, Fisher's Exact and the Odds Ratio (OR) with significance level ˂ 0.05. The results showed a high coverage of prenatal care in Sergipe (99.3%; n= 763), but little more than half of these women initiating prenatal care before 16 weeks of gestation (57%; n= 435) and 74.7% (n= 570) having six or more number of appointments. Only 61.3% (n= 468) were advised about which maternity care service to give birth and 29.4% (n= 226) reported searching more than one health service for admission in labour and birth. The antenatal peregrination was higher among women who performed the prenatal care with nurse in the majority of the consultations (OR: 2.05, 95% CI: 1.49-2.83), and was less frequent among women aged ≥ 20 years (OR: 0.50, 95% CI: 0.34-0.71), with high education level (OR: 0.42, 95% CI: 0.31-0.59), paid work (OR: 0.61 95% CI: 0.44-0.85), and prenatal care performed in a private service (OR: 0.21, 95% CI: 0.12-0.36). Cesarean section was performed in 40.6% (n= 312). The variables associated with the initial women's preference for cesarean section were age ≥ 20 years (OR: 1.94, 95% CI: 1.21-3.11) and paid work (OR: 1.52, 95% CI: 1, 08- 2.13). The choice by cesarean section at the end of gestation was associated with prenatal care in private service (OR: 2.50; 95% CI: 1.56-4.01) and was less frequent among the women who performed the prenatal care with nurse in the majority of the consultations (OR: 0.25; 95% CI: 0.11-0.60). It was concluded that the prenatal care in Sergipe does not offer satisfactorily the activities established by the PHPN and that there are a high antenatal peregrination and cesarean sections, being influenced by maternal socioeconomic factors and by the characteristics of the prenatal care.